Seminar Kewirausahaan – Cara Cerdas Mengubah Masalah Menjadi Peluang Usaha PPGT Nonongan SALU - Mince Batara; Ellyn Patadungan; Rati Pundissing (Universitas Kristen Indonesia Toraja, 2023)
The church is a community, like organizations in general, the church has an important role in the lives of its congregation members. In the organizational structure, each church has an intra-ecclesiastical administrator. The Administrators of each congregation will be representatives of each congregation. PPGT Class PPGT OIG Nonongan Salu conducted an entrepreneurship seminar with the aim of providing knowledge, motivation and preparing Christian youths who are independent and become agents of change for themselves, the congregation and the nation. Entrepreneurship seminar activities in the Sub Theme: Smart Ways to Turn Problems into Business Opportunities. This activity is attended by more than ± 30 people.